Effectiveness of plant growth regulator fertilizers on the recovery of pepper plants under water stress conditions - Long, Nguyen Viet; Phommalueza, Dokmai; Nhung, Phan Thi Hong; Ha, Chu Duc; Loc, Nguyen Van (Australian journal of crop science, 2025)
This study examined the effects of three plant growth regulator fertilizers (Atonick, N3M, and Profarm) on the performance of black pepper (Piper nigrum) under various water stress conditions (drought, waterlogging, and control). Conducted in a greenhouse over a two-month period from June to July 2024 using sandy clay-loam soil, the study employed a Randomized Complete Block Design with ten replicates (each plant was used as a replicate) to measure growth parameters, such as plant height, number of leaves, branches, stem diameter, leaf area, fresh weight, and dry weight. Results showed that N3M significantly enhanced growth under drought stress, with plant height reaching 32.99 cm, leaf count 11.78, and dry weight 6.02 g after two weeks, compared to the control's 29.78 cm, 10.33 leaves, and 4.56 g, respectively. These findings confirm N3M's superior efficacy in improving black pepper growth under water stress. Compared to Atonick and Profarm, N3M’s balanced macronutrient and micronutrient content, including nitrogen, phosphorus, potassium, and trace elements of plants, played a crucial role in maintaining physiological functions and mitigating the adverse effects of environmental stress. The results suggest that targeted nutrient supplementation, particularly with N3M, can optimize black pepper's resilience under water stress conditions, contributing to better agricultural management practices in the face of climate change. Further research is recommended to explore the long-term impacts of these fertilizers across varying environmental conditions to enhance crop resilience more broadly.